Reduksi Waktu Tunggu di Unit Rawat Jalan Rumah Sakit - A Heri Iswanto (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Waiting time for medical services determines the efficiency and quality of client hospital services. The aim of this study was to determine the average length of outpatient waiting time using the Malcolm Baldridge system in the health sector and other relevant factors including leadership, strategic planning, customer focus, measurement, analysis and knowledge management. The survey method used in the definition was completed and enriched. with critical analysis. Collecting detailed quantitative data on patient monitoring, counting and registration. Appropriate documents were obtained through extensive research and investigation of related documents. Research finding the average waiting time for patients is 66.58 minutes per patient, exceeding the average working time of 60 minutes According to the Ministry of Health of the Republic of Indonesia,